Interface Control Between Amorphous Silicon and Polymer Subcells in Tandem Solar Cells Using Graphene Interlayer - Kim, Chulki; Kim, Taehee; Han, Seunghee; Kim, Il Won; Lee, Sang-Soo; Son, Hae Jung; Kim, Heesuk (AMER SCIENTIFIC PUBLISHERS, 2016)
As commercial interest in energy-harvesting devices has increased, tandem solar cells composed of two or more stacked photoactive layers have attracted interest in the field of solar cell technology. In hybrid tandem solar cells connected by an internal junction, interface control between subcells is very important for high performance. We report an organic inorganic hybrid tandem solar cell containing a reduced graphene oxide (rGO) interlayer between an inorganic amorphous silicon subcell and an organic photovoltaic cell (OPV). The transparency and hydrophilicity of the rGO thin layer spray-coated onto the amorphous silicon photovoltaic cell improved compatibility with the upper poly(3,4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) layer of the OPV subcell, thus decreasing the series resistance of the hybrid tandem cell. As a result, charge recombination occurred more efficiently between electrons and holes generated in the amorphous silicon front cell and the OPV back cell, respectively, and the photovoltaic performance of the tandem solar cell was enhanced. These results demonstrate that graphene is a good material for the interlayer component of organic inorganic hybrid tandem solar cells.
Keywords: POWER CONVERSION EFFICIENCY; OXIDE; REDUCTION; FILMS; SHEETS; GROWTH; CARBON; LAYER